An Environmental Study of Epiphytic Algae on Ceratophyllum demersum in Tigris River within Baghdad City, Iraq - Baghdad Science Journal (Baghdad Science Journal, 2014)
The present study was conducted in the Tigris River within Baghdad (University of Baghdad campus). The study included some physicochemical parameters and qualitative of epiphytic algae on the host plant (Ceratophyllum demersum) during summer season 2013. The results revealed that the study area was alkaline, hard and oxygenated water. A total of 105 taxa of epiphytic algae was identified. Bacillariophyceae diatoms composed 44.7% of the total and were represented by 42.4% of the order Pennales and 1.9 %of the order Centrales. Chlorophyceae composed 32.3%, followed by Cyanophyceae composed 22.8 % of the total. The total number of epiphytic algae was fluctuated among the study period. Most of the identified algae were benthos type and a few was phytoplankton such as: Cyclotella spp, Coscinodiscus sp, Bacillaria paxillifer and Scenedesmus spp. Seventeenth species found in all the study period.